Shear behavior of hybrid fiber reinforced concrete (HFRC) beams without web reinforcement - Ulu, Adem Afşın. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
This study was conducted to investigate the effects of hybrid fiber combinations on shear capacity of large size reinforced concrete beams. Ten hybrid fiber reinforced concrete beams were cast. Fiber volume was varied from 0% to 1.5%. Two fibre types (RC-65/35-BN and RC-80/60-BN) were used for the hybrid combinations. In addition to that, two types of shear span-to-effective depth ratios (a/d) (2 and 3.75) were used. Four-point bending tests were applied to examine shear behavior. Effects of shear span to effective depth ratio, fiber volume, hybrid combination on mechanical performance were discussed. Moreover, results of this study was compared with the results of a previous study (S¸en, 2009) in order to observe the differences between hybrid and one type of fiber reinforcement. The test results showed that all the beams with an a/d ratio of 2 failed under shear compression type of failure. On the other hand, the beams with an a/d of 3.75 failed under diagonal tension type of failure. When results were examined, failure mode was found to not change with increasing fiber volume ratio. Average stresses at first crack formation and at ultimate were found to decrease when shear span-to-effective depth ratio increased. These results were consistent with the results of the previous study (S¸en, 2009) and available literature. Shear capacity of the beams were found to increase with increase in fiber volume ratio. The greatest increase was observed when fiber volume ratio was increased from 0.5 to 0.75%. Fiber contribution was found to vary for different failure modes. Fiber contribution was higher when a/d ratio was small. This is due to different failure modes occurring for different a/d values. When a/d ratio is 2, shear compression failure occurred. In this type of failure, crack was found to open wider before the specimen failed when compared to the diagonal tension failure (observed when a/d is 3.75). Therefore, effect of using fibers was more pronounced when a/d value was 2.0. When the results of this study were compared with the results of a previous study (S¸en, 2009), in which similar specimens and testing set-up were used, hybrid combinations were found to be more effective in increasing shear capacity compared to single type of fiber reinforcement. This is explained by more effective crack arresting mechanism in case of hybrid combination. Using two sizes of fibers are useful since different size of cracks were captured and arrested at different meso and macro levels.
Keywords: Mechanical engineering -- Hybrid composite.